Meta-Analysis: Basic Education Literacy Issues in The 21st Century: Meta Analisis: Isu-Isu Literasi Pendidikan Dasar di Abad Ke-21 - Anggraini, Gian Fitria; Sunendar, Dadang; Rahman (Pedagogia : Jurnal Pendidikan, 2023)
The development of Indonesian children's reading literacy is of particular concern, especially with the decline in the reading ability index, both according to PIRLS and PISA data, from year to year. The decline in reading literacy skills is of particular concern to the Indonesian government. Through various literacy programs, the government is trying to improve literacy skills. Several issues related to children's literacy skills related to the contribution of society, especially family, in encouraging a culture of literacy. This study attempts to examine and analyse issues related to basic educational literacy, both those related to the contribution of family literacy, digital and critical literacy. This research used a qualitative approach with a literature review. Data analysis was carried out narratively by collecting data in the form of documents (books, journal articles, research results). The results of the analysis show that the challenges of basic education literacy issues, especially in the 21st century, will be related to the readiness and contribution of society, especially family and school, and how society can face the challenges of information technology through critical digital literacy that is relevant and meaningful for children.